Flexible PolyCMUTs: Fabrication and Characterization of a Flexible Polymer‐Based Capacitive Micromachined Ultrasonic Array for Conformal Ultrasonography. Issue 5 (4th December 2022) - Omidvar, Amirhossein; Cretu, Edmond; Rohling, Robert; Cresswell, Mark; Hodgson, Antony J.
Abstract: Conventional ultrasound transducers are short and rigid, which limits their applications, especially in the area of musculoskeletal imaging where many of the structures to be imaged lie within long curved anatomical structures, such as limbs. In such cases, conformal ultrasound imaging can be advantageous. This paper presents a process for fabricating 1D and 2D flexible polymer‐based capacitive micromachined ultrasound transducers (flexible CMUTs). As a proof of concept, all elements of a 32‐element linear flexible array are shown to be functional (100% yield) and uniform in fundamental resonant frequency (SD = 1.8%). One‐way and two‐way acoustic responses during immersion tests in flat, convex, and concave array configurations (radii of curvature = 3 cm) show an average fractional bandwidth of 83% and 75%, respectively, across these bending conditions. The flexible array shows no signal drop after over 100 bending cycles and only 6% variation in pulse amplitude after over 14 h of continuous operation. Finally, the resulting transducers are shown to operate at up to 15 MHz. The findings demonstrate robust operation of flexible CMUT arrays and justify further development targeted at key imaging applications, particularly in the area of diagnosing musculoskeletal conditions. Abstract : This paper presents a novel fabrication technique for making 1D and 2D flexible polymer‐based capacitive micromachined ultrasonic transducers (flexible polyCMUTs). Comprehensive characterization tests are conducted to verify the functionality of these transducers. Acoustic measurements confirm the mechanical durability of these arrays under bending conditions—for the first time—and suggest they can potentially be used for wearable imaging applications.